Combustion performance and emissions of 2-methylfuran diesel blends in a diesel engine. (1st July 2016) - Xiao, Helin; Zeng, Pengfei; Li, Zhongzhao; Zhao, Liangrui; Fu, Xiaowei
Highlights: This is the first comprehensive study of diesel–MF blends in CI engine. Ignition delay, combustion duration and emissions were studied. Soot emission from diesel–MF blends are much less than pure diesel. High MF fraction in fuel blends is not suitable for CI engine. Abstract: As an important renewable engine fuel, 2-methylfuran (MF) has drawn intense attention due to the breakthroughs in its production methods. In the present study, combustion characteristics and emissions of a four cylinder direct-injection compression-ignition (DICI) engine fueled with diesel–MF blends (DM) and pure diesel are investigated. The tests were performed at constant speed of 1800 rpm and varying loads from 0.13 to 1.13 MPa brake mean effective pressure (BMEP). Results show that diesel–MF blends have different combustion performance from pure diesel. The combustion phase of fuel blends is retarded with the increase of MF fraction. Diesel–MF blends are characterized with longer ignition delay and shorter combustion duration. Meanwhile, diesel–MF blends show higher brake thermal efficiency (BTE) than pure diesel. However, diesel–MF blends lead to higher NO x emissions than pure diesel and the NO x emissions are increased with the increase of MF fraction. The soot emissions from diesel–MF blends are significantly reduced compared to pure diesel. The CO and HC emissions from tested fuels are nearly the same at medium and high engine loads. Pure diesel produces lower CO emissions and higher HC emissions than that of diesel–MF blends at low loads of 0.13–0.38 MPa BMEP.